Gate-damage accumulation and off-line recovery in SiC power MOSFETs with soft short-circuit failure mode. (November 2020) - Castellazzi, A.; Richardeau, F.; Borghese, A.; Boige, F.; Fayyaz, A.; Irace, A.; Guibaud, G.; Chazal, V.
Abstract: This paper proposes the detailed analysis of the short-circuit failure mechanism of a particular class of silicon carbide (SiC) power MOSFETs, exhibiting a safe fail-to-open-circuit type signature. The results are based on extensive experimental testing, including both functional and structural characterisation of the transistors, specifically devised to bring along gradual degradation and progressive damage accumulation. It is shown that the soft failure feature is associated with degradation and eventual partial shorting of the gate-source structure. Moreover, partial recovery, induced here by ad-hoc off-line biasing, is observed on degraded components. The results indicate that it is a realistic new option for deployment in the application to yield enhanced system level robustness and system-level hopping-home operational mode capability, of great importance in a number of reliability critical domains, such as, for instance, transportation.